Mechanical parameters and flight phase characteristics in aquatic plyometric jumping - Louder, T. J.; Searle, C. J.; Bressel, E. (Sports Biomechanics, 2016)
Plyometric jumping is a commonly prescribed method of training focused on the development of reactive strength and high-velocity concentric power. Literature suggests that aquatic plyometric training may be a low-impact, effective supplement to land-based training. The purpose of the present study was to quantify acute, biomechanical characteristics of the take-off and flight phase for plyometric movements performed in the water. Kinetic force platform data from 12 young, male adults were collected for counter-movement jumps performed on land and in water at two different immersion depths. The specificity of jumps between environmental conditions was assessed using kinetic measures, temporal characteristics, and an assessment of the statistical relationship between take-off velocity and time in the air. Greater peak mechanical power was observed for jumps performed in the water, and was influenced by immersion depth. Additionally, the data suggest that, in the water, the statistical relationship between take-off velocity and time in air is quadratic. Results highlight the potential application of aquatic plyometric training as a cross-training tool for improving mechanical power and suggest that water immersion depth and fluid drag play key roles in the specificity of the take-off phase for jumping movements performed in the water.